2003
DOI: 10.3732/ajb.90.12.1669
|View full text |Cite
|
Sign up to set email alerts
|

Development of biochemical specialization and organelle partitioning in the single‐cell C4 system in leaves of Borszczowia aralocaspica (Chenopodiaceae)

Abstract: The terrestrial plant Borszczowia aralocaspica (Chenopodiaceae) has recently been shown to contain the entire C(4) photosynthesis mechanism within individual, structurally and biochemically polarized chlorenchyma cells rather than in a dual cell system, as has been the paradigm for this type of carbon fixation (Nature 414: 543-546, 2001). Analysis of carbon isotope composition and (14)CO(2) fixation shows that photosynthesis and growth of B. aralocaspica occurs through carbon acquired by C(4) photosynthesis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
44
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 34 publications
5
44
0
Order By: Relevance
“…Studies of this type on plants and macroalgae have dealt specifically with changes in chloroplast position in response to light intensity. The single-cell C 4 systems appear unique in that, early in leaf development, chloroplasts become separated into two cytoplasmic compartments and thereafter remain anchored (Voznesenskaya et al, 2003. This partitioning of chloroplasts in mature chlorenchyma cells does not change during the night or under different light conditions (E. Voznesenskaya, N. Koteyeva, S.D.X.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of this type on plants and macroalgae have dealt specifically with changes in chloroplast position in response to light intensity. The single-cell C 4 systems appear unique in that, early in leaf development, chloroplasts become separated into two cytoplasmic compartments and thereafter remain anchored (Voznesenskaya et al, 2003. This partitioning of chloroplasts in mature chlorenchyma cells does not change during the night or under different light conditions (E. Voznesenskaya, N. Koteyeva, S.D.X.…”
Section: Discussionmentioning
confidence: 99%
“…Seeds of Bienertia sinuspersici and Suaeda aralocaspica (formerly Borszczowia aralocaspica) (Schü tze et al, 2003;Voznesenskaya et al, 2003) were germinated on moist filter paper at room temperature. Seedlings were then transferred to 4-inch pots containing a soil mixture of 2 parts commercial potting soil, 1 part clay soil, 1 part sand, 0.5 parts Perlite, and 0.5 parts dolomite powder and were watered three times per week and once every week with MiracleGrow Excel 21-5-20 fertilizer and a salt solution (0.150 M NaCl).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…1O). In previous studies, it has been shown among various C 4 species in family Chenopodiaceae that only Rubisco-containing chloroplasts tend to accumulate starch (Voznesenskaya et al, 1999(Voznesenskaya et al, , 2003(Voznesenskaya et al, , 2005. In leaves of both Kranz and singlecell C 4 species, starch accumulates in mature Rubiscocontaining chloroplasts and not in chloroplasts specialized to support the synthesis of C 4 acids by generating the substrate for PEPC.…”
Section: It and M Leavesmentioning
confidence: 99%
“…Nevertheless, three succulent species in family Chenopodiaceae, Bienertia cycloptera, Bienertia sinuspersici, and Suaeda aralocaspica (formerly classified as Borszczowia), were shown to have a unique mechanism of C 4 photosynthesis that occurs within individual photosynthetic cells (single-cell C 4 anatomy) by intracellular partitioning of enzymes and organelles (including dimorphic chloroplasts) into two compartments (Voznesenskaya et al, 2001(Voznesenskaya et al, , 2002Edwards et al, 2004;Akhani et al, 2005). S. aralocaspica has a single layer of elongated, cylindrical chlorenchyma cells in which functions of C 4 photosynthesis are spatially separated to opposite ends of the cells (Voznesenskaya et al, 2003). B. cycloptera and B. sinuspersici have an unusual development of two cytoplasmic compartments in chlorenchyma cells, consisting of a large central cytoplasmic compartment (CCC) packed with chloroplasts and mitochondria and a peripheral layer of cytoplasm with chloroplasts (Voznesenskaya et al, 2002(Voznesenskaya et al, , 2005Akhani et al, 2005).…”
mentioning
confidence: 99%
“…As well as this diversity within the biochemistry of C 4 photosynthesis, there is also variation in terms of the leaf anatomy associated with the C 4 pathway. Although several examples of C 4 photosynthesis operating in single cells have been described (Reiskind et al, 1997;Casati et al, 2000;Reinfelder et al, 2000;Voznesenskaya et al, 2002Voznesenskaya et al, , 2003, most C 4 species compartmentalize carboxylation and decarboxylation activities into two distinct cell types. At least 22 variations of two-celled "Kranz" anatomy have been documented (Dengler and Nelson, 1999;Edwards and Voznesenskaya, 2011;Sage et al, 2012) whereby different cell types have been coopted as the photosynthetic carbon assimilation and photosynthetic carbon reduction tissue.…”
mentioning
confidence: 99%